1994
DOI: 10.1007/bf01715495
|View full text |Cite
|
Sign up to set email alerts
|

Moderne topische Glukokortikoide und Antiinfektiva beim superinfizierten atopischen Ekzem: Bilden Prednicarbat und Dodecyldimethylammoniumchlorid eine rationale Kombination?

Abstract: The addition of an anti-infective to a topical glucocorticoid preparation for superinfected atopic eczema is still controversial. To address this question in the context of the topical glucocorticoids of the non-halogenated double-ester type 0.25% prednicarbate cream was compared to the identical preparation incorporating the same amount of the disinfectant didecyldimethylammoniumchloride in patients suffering from atopic eczema carrying Staphylococcus aureus at a density of more than 10(6) colony-forming unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…This indicates that the reduction of S. aureus is probably a secondary phenomenon, possibly being due to less favorable skin conditions for colonization. It could also explain why in studies, in which potent topical glucocorticosteroids were applied for a period of 7 days or longer, a significant reduction of S. aureus was demonstrated that was not substantially increased by combining the steroid with an antibiotic [19, 20]. However, data about the kinetics of antibacterial and clinical efficacy are lacking in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the reduction of S. aureus is probably a secondary phenomenon, possibly being due to less favorable skin conditions for colonization. It could also explain why in studies, in which potent topical glucocorticosteroids were applied for a period of 7 days or longer, a significant reduction of S. aureus was demonstrated that was not substantially increased by combining the steroid with an antibiotic [19, 20]. However, data about the kinetics of antibacterial and clinical efficacy are lacking in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…19 Another study of prednicarbate 0AE25% cream plus didecyldimethyl-ammonium chloride 0AE25% vs. prednicarbate 0AE25% cream in adults found no significant difference in global outcome at the end of treatment (RR 0AE64, 95% CI 0AE25-1AE68). 24 Isolation of S. aureus was similar between the two groups at the end of the study.…”
Section: Clinically Infected Eczemamentioning
confidence: 92%
“…Adverse events requiring withdrawal from treatment.Study or SubgroupKorting et al (1994)24 Wachs et al (1976)19 …”
mentioning
confidence: 98%
“…Since the effectiveness of combining topical antibiotic or anti-infective agents with glucocorticosteroids is still controversially discussed [30], textiles with antibacterial qualities may offer the advantage of enhancing the clinical efficacy of glucocorticosteroid or other anti-inflammatory therapy. In addition, an identical clinical efficacy might be achieved by combining textile antistaphylococcal treatment and steroids of less potency and in this way reducing possible side effects of glucocorticosteroids.…”
Section: Discussionmentioning
confidence: 99%